Open Banking Adoption and Banking Competition: Implications for Lending Rates & Disintermediation - Zaluku, Siska (Cattleya Darmaya Fortuna, 2025)
This study examines the impact of Open Banking adoption onlending rates, spreads/NIMs, and banking disintermediation inIndonesia. Using a quarterly bank-level panel (2018–2025) and acausal identification strategy—a dynamic panel (System-GMM) tocapture credit price persistence, and stepwise difference-indifferences(DiD) with event study—we construct a composite OpenBanking Index (OBI) from four pillars: API readiness, API usage,data openness, and partnership depth. Results show that anincrease in OBI is negatively and significantly correlated withlending rates and NIMs; DiD estimates show a decline in lendingrates immediately after adoption and a plateau within 4–6 quarters,while a decline in LDR indicates moderate disintermediation.Mechanism analysis indicates competition as the primarytransmission channel: OBI lowers the Lerner Index and makes theBoone indicator more negative, thereby suppressing bank pricingpower. Nonlinearity with the OBI maturity threshold (≈70/100)above which the interest rate reduction effect is amplified is found,as well as greater heterogeneity among small/medium banks, morecompetitive markets (low HHI), and banks with high digital maturity.The findings suggest a policy focus on deepening theimplementation of Open Banking (API interoperability, consentmanagement, fair access) to balance innovation, competition, andbanking system stability.